Clustering by the level of demographic potential of the regions of Kazakhstan based on SPSS - Rakhmetova, R.; Kaliyeva, S.; Andekina, R.; Maxyutova, A. (BUKETOV BUSINESS REVIEW, 2022)
Object: Based on a statistical analysis of the demographic development of the regions of Kazakhstan for the period from 1999 to 2020, to group the regions according to the main demographic indicators and conduct a comparative analysis and assessment. Methods: Correlation-regression analysis, comparative analysis, multivariate statistical and mathematical method, special computer program SPSS. Results: A comparative dynamic analysis of the regions of Kazakhstan between clusters for the period from 1999 to 2020 was carried out. As a result of the analysis, it was found that the main demographic indicators differ by clusters up to 2-3 times. Conclusions: In general, the demographic development has been slow throughout the country over the years, and regions have been identified that are oriented towards a regressive way of development. First of all, it is proposed to solve the demographic problem of these regions in order to enter the way of progressive demographic development in the country as a whole.